Psychometric evaluation of a caregiver diary for the assessment of symptoms of respiratory syncytial virus - Valerie Williams; Carla DeMuro; Sandy Lewis; Nicole Williams; Todd Wolynn; Paul Wisman; Stan L. Block; Shelly Senders; Seth Toback; Jason W. Chien (SpringerOpen, 2018)
Abstract Background There are no clinical outcome assessment (COA) tools developed in accordance with Food and Drug Administration (FDA) guidance suitable for the evaluation of symptoms associated with respiratory syncytial virus (RSV) infection among infants. The Gilead RSV Caregiver Diary (GRCD) is being developed to fulfill this need; the present research evaluates the GRCD and documents its reliability, validity, and responsiveness among children < 24 months of age with acute RSV infection. Methods A prospective, observational study was conducted in the United States during the 2014-2015 northern hemisphere winter season. Subjects were < 24-month, full-term, previously healthy infants with confirmed RSV infection and ≤5 days of symptoms. The GRCD was completed twice daily for 14 days by caregivers. Additional data were collected during the initial visit, subsequent visits, and end-of-study interview. Test-retest reliability (kappa and intraclass correlation coefficients [ICCs]), construct validity (correlations and factor analyses), discriminating ability (analyses of variance and chi-square), and responsiveness (effect sizes and standardized response means) were evaluated. Results A total of 103 subjects were enrolled (mean age 7.4 ± 5.3 months). GRCD items were grouped into different subscales according to question content, which, with the exception of the behavior impact domain (ICC = 0.43), demonstrated internal consistency (alphas = 0.78-0.94) and test-retest reliability (ICCs = 0.77-0.94). Hypothesized correlations with parent global ratings of RSV severity ranged from 0.45 to 0.70 and provided support for construct validity. Support for discriminating ability was limited. Effect sizes ranged from − 1.48 to − 4.40, indicating the GRCD was responsive to change. Conclusions These psychometric analyses support the validity, reliability, and responsiveness of the GRCD for assessing RSV symptoms in children < 24 months of age.